Simplificar para traducir documentos negociales de la Common-law: los esquemas básicos del derecho al servicio del traductor jurídico no jurista - Ferran Larraz, Elena (The Journal of Specialised Translation, 2012)
It is a well-known fact that the lay translator in legal matters may find it very difficult to understand the common-law document to be translated. It is mainly because he does not know about law and its basic principles and institutions. Thus, in the context of the translation of documents of disposition of the common-law, and particularly in relation to Sales deeds, we put forward now several textual analysis techniques leading to the acquisition of cognitive competence by the lay translator or else the student of legal translation. The strategies devised should result in a new definition of a new jurilinguistic function (Ferran: 2004): the function of disposition of property and its sub-function, the function of warranty of title. They should also result in the acquisition of several procedures related to the translation process that are encouraging the translator to the following: (1) verify the basic schema of the document of disposition; (2) classify and compare the minor resulting functions to be collected in a 'glossary of functions;' (3) carry out the necessary documentation to obtain the relevant terminological pairs Common-Law – Spanish-Law and, finally (4) control the translation and resulting target text, bearing always in mind the basic schema, the glossary of functions and the glossary of terms.